Russian counter-trade as a mechanism for promoting arms sales and diplomatic influence - Anicetti, Jonata; Wu, Shang-Su; Matthews, Ron (Cambridge University Press (CUP), 2025)
Why and how does Russia engage in the arms trade? Scholars have largely focused on why Russia participates in the arms trade, often neglecting the equally crucial question of how it conducts this trade. Yet understanding the mechanisms by which Russia promotes arms sales provides deeper insights into why it does so. While many portray Russia’s arms trade as driven by economic or strategic motivations, few examine the specific tools it employs, particularly defence counter-trade, which includes non-monetary barter, counter-purchase obligations, and industrial or technological investments (offsets). This paper fills that gap by offering an eight-decade perspective on Russian arms trade practices, drawing on data and case studies to uncover a more nuanced set of motives. Russia integrates economic and political objectives in its arms trade, seeking not only to out-compete Western suppliers but also to expand or regain influence in various regions, circumvent Western-imposed sanctions, secure access to valuable resources, and sustain its military capabilities. Although barter and technological cooperation have long been part of its trade practices, Russia has only recently adopted offset practices in a systematic way. By leveraging defence counter-trade, Moscow aims to stabilise, and potentially grow, its arms exports as global conditions shift.counter-trade
Keywords: 4408 Political Science; 44 Human Society; 4404 Development studies; arms trade; counter-trade; defence; diplomacy; offsets; Russia